Prevalence and Factors Affecting Child Marriage Practice among Rural Indigenous Communities in Sibu, Sarawak - Rosalia, Saimon; Ali, Puji; Razitasham, Safii (Human Resource Management Academic Research Society, 2021)
Child marriage could impinge the accomplishment of at least six out of eight of the Sustainable Development Goals (SDG). Malaysia recorded an average of 1000 child marriage applications annually. Sarawak recorded the highest child marriage cases. This study aimed to determine the prevalence and factors affecting child marriage among rural indigenous communities in Sibu, Sarawak, Malaysia. A validated questionnaire assessed the socio-demographic, knowledge on marriage law, and perceptions on child marriage factors among 244 respondents, aged between 13 to 50 years old. The mean age of the respondents was 34.9 (SD=10.4) years old. The prevalence of female child marriage was as high as 13.2%. More than 50% respondents perceived that child marriage could protect girls from premarital sex and unwanted pregnancy. Almost all respondents (91%) have a misconception about the minimum age of marriage. Education and gender were significant factors that explained about 25% of the total variance of the child marriage occurrence. Based on these findings, there is an urgency for an effective education for sexual health among teens to prevent teenage pregnancy; reformation of the educational system for each child to complete their secondary education up to Form 5; and certainly to establish a clear legal age for marriage at 18 consistent with the international standard.